Participação da via alfa-2 adrenérgica no controle da secreção do hormônio do crescimento no período prépúbere em novilhas da raça Nelore - de Oliveira Santana Batista, Emiliana [UNESP]; Cardoso, Daniel; de Paula Nogueira, Guilherme [UNESP] (My University, 2011)
This study investigated GH secretion after clonidine (alpha-2 adrenergic agonist) treatment in pre-pubertal Nelore heifers. Clonidine (10 mg/kg, IV, 15 min samples for 4 h) was administrated in the same Nelore heifers at eight (n = 4), 12 (n = 5) and 15 (n = 4) months of age. The GH concentration was measured by radioimmunoassay (sensivity = 0.25 ng/mL, CV = 16%). At eight months, clonidine increased GH average concentration, total area of peaks, the total area of GH secretion and increased peak amplitude and reduced time to onset of peak (P < 0.05). At 15 months, the administration of clonidine increased the GH average concentration and at 12 months the increased occurred only in restricted intervals (P < 0.05). Clonidine injection stimulated GH secretion in prepubertal heifers and this effect was more evident in Nelore heifers at eight months compared to 12 and 15 months of age.
Participation of the pathway alfa-2: Adrenergic in the control of growth hormone secretion in the pre-puberty period of the Nellore heifers
Keywords: Clonidine; GH; Nelore; Prepubertal